EFECTO DEL TOLTRAZURIL Y LA COMBINACIÓN DE SULFADOXINA Y PIRIMETAMINA EN EL TRATAMIENTO DE LA SARCOCISTIOSIS CANINA DURANTE EL PERIODO PATENTE. - Barrientos V., María (2007)
The objective of this study was to evaluate the efficacy of toltrazuril (2.5)% and the combination of sulfadoxine and pirimetamine (500-25 mg) on the treatment of canine sarcocystiosis. The study was conducted from October 2005 until March 2006 in the Experimental Station of the IVITA Research Center, Maranganí, Cusco. A total of 15 crossbred puppies, both sexes, 2-4 months of age, that were dewormed and fed with a diet extent of meat were used. Puppies were infected with approximately 9,000- 10,000 cysts of Sarcosystis lamacanis present in 4-5 g of alpaca heart. Feces were daily collected and analyzed to observe the presence of sporocysts or oocysts. Then, were distributed in three groups of 5 animals each. One group remained untreated (as control) and the other two groups were daily treated during 10 days with 15 mg/kg of toltrazuril (2.5%) or the combination of sulfadoxine and pirimetamine (500-25 mg) in a dose of 20 and 1 mg/kg respectively. Fecal samples were daily collected and analyzed by the flotation method using the Sheather solution to determine the presence of sporocysts or oocysts and the modified Stoll method to quantify the number of eggs per gram of feces. The results showed that the efficacy of toltrazuril in the control of sarcosystiosis was 94.7% at the 3rd day of treatment and 100% at day 6, whereas the combination of sulfadoxine and pirimetamine did not control it, and only a moderate efficacy (88.1%) was observed in the 2nd day.